CHARACTER BUILDING OF TOM SAWYER IN MARK TWAIN’S THE ADVENTURES OF TOM SAWYER - RAMADHANI, MOHAMAD ARLI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Novel, as one of literary works, can be a representation of the real life thatportrays the social and cultural phenomena in a certain society. Novel can be used as thedescription of the influence of society towards the character building of the charactersof  the  novel  as  individual.  In  Mark  Twain’s  The  Adventures of  Tom  Sawyer,  thecharacter building of Tom Sawyer, as the main character, is influenced by the Southsociety in America, which also leads to the development of Tom Sawyer’s personalitiesis implicitly and explicitly shown. The study applies socio-cultural approach as the grounding theory to find out thesocial and cultural phenomena of the South society which influences Tom Sawyer’scharacter building. The background of Mark Twain in terms of The Adventures of TomSawyer novel and the socio-cultural life in the South society are used to provide somesupporting information to make the analysis and interpretation of the study becomesmore comprehensive. The  result  of the  study reveals  that  Mark Twain’s The Adventures of  TomSawyer  elevates  the  socio-cultural  issues  in  the  South  society  that  influence  thecharacter building of Tom Sawyer. The relationship between Tom Sawyer and theSouth  society and  the  psychological process  within  Tom  Sawyer’s personalities isclearly described. However, because this novel does not merely elevate socio-culturalaspects, it is suggested for the next researchers to research it from other perspectives,such as economic condition, racism, or Christian cultural values.Keywords:  Mark  Twain,  The  Adventures  of   Tom  Sawyer,  character  building,personalities, socio-cultural approach